The accuracy of magnetic resonance imaging (MRI) in predicting the invasion of the tunica albuginea and the urethra during the primary staging of penile cancer. (3rd June 2015) - Hanchanale, Vishwanath; Yeo, Lehana; Subedi, Nawraj; Smith, Jonathan; Wah, Tze; Harnden, Patricia; Bhattarai, Selina; Chilka, Sameer; Eardley, Ian
Abstract : Objectives: To assess the accuracy of magnetic resonance imaging (MRI) in predicting invasion of the tunica albuginea (TA) and the urethra during the primary staging of penile cancer. Patients and Methods: In all, 104 consecutive patients with clinical T1–T3 penile cancer had a penile MRI as a part of local staging protocol. An artificial erection was induced before MRI by injecting alprostadil (prostaglandin E1 ). Four men with poor quality MRI images were excluded from the study. The preoperative MRI was compared with final histology to assess its accuracy in predicting the invasion of the TA and urethra. Results: Data of 100 patients who underwent penile MRI before definitive surgery for invasive penile carcinoma were available for analysis. The mean age was 65 years and number of patients with pathological stage T1, T2 and T3 was 32, 52, and 16, respectively. The sensitivity and specificity of MRI in predicting the invasion of TA and urethra was 82.1% and 73.6%, and 62.5% and 82.1%, respectively. There were no MRI‐related complications. Conclusions: This study shows that penile MRI is an accurate method for assessing TA invasion but is less sensitive in assessing urethral invasion. These results support the use of MRI in the local staging of penile cancer.